Membebaskan Waktu, Merajut Kembali Kemanusiaan: Refleksi Filosofis Tentang Tahun Yubileum - Watu, Virgilio Yogie Damiano Beke (Riviera Publishing, 2025)
The Jubilee Year, a tradition rooteed in Judaism and adopted by the Catolic Church, is a special moment the amphasizes forgiveness, liberation, and renewal. This articel aims to examine the Jubilee Year from a philosophical perspective, particulary in the context of liberating time and reveawing humanity. Through a qualitative approach with a literature study method, this research explores the philosphical meaning behind the practice of the Jubilee, how the concept is relevant to the existential condition of humans, and how human values can be strengthened through the celebration of the Jubilee. The analysis will include a review of the concepts of time, justice, forgiveness, community, and hope within a relevant philosphical framework. This article argues that the Jubilee Year offers a profound philosophical framework for understanding the journey of human life as an effort to free oneself from the shackles of the past and reweave harmonious relationship with others and the environment, because philosophy invites us to continue to reflect on the meaning of life and seek the truth.